Bare‐difference methodology and the scientific analogy. (6th March 2021) - Kopeikin, Zak A.
Abstract: The bare‐difference methodology is considered to be a powerful tool in ethical reasoning. The underlying idea is that we can identify the intrinsic evaluative significance of some feature by constructing contrast cases or bare‐difference cases, i.e., two cases that hold everything constant but for the feature of interest. While this popular methodology has been challenged by prominent philosophers such as Kagan, Thomson, and Kamm, it is intuitively appealing because, as Perrett identifies, the methodology appears to share the same logical structure as a fruitful scientific procedure. In this paper, I argue that examining this 'scientific analogy' is crucial to understanding both the limitations and the prospects for ethical bare‐difference reasoning. I expand upon Perrett's discussion of the scientific analogy and examine another relevant similarity. I then highlight two relevant dissimilarities between ethical bare‐difference reasoning and its scientific analogue. Though these differences threaten to undermine the analogy, I show how the analogy might be mended to better bring the ethical methodology in line with its scientific counterpart and avoid challenges to ethical bare‐difference methodology raised by philosophers in the literature.